Thank You Email from Lupe Anguiano Regarding Ventura County Climate Change Hero Award - Lupe Anguiano::::::
Dear John, Million thanks for honoring me with the Ventura County Climate Change Hero Award. I was truly surprised and delighted to have been chosen out of so many worthy candidates...